Keseimbangan Jangka Panjang antara Variabel Makro Ekonomi dengan Indeks Harga Saham - Adisetiawan, R (Jurnal Trikonomika, 2011)
The economic condition of a good country usually characterized by the reduced amount of money in circulation, declining inflation, a stronger exchange rate of IDR/USD, as well as the decline in interest rates. This study aims to determine whether there is a balance of long-term and simultaneous relationships between macroeconomic variables (inflation, BI rate, 1-month deposit interest rate, money supply and exchange rate IDR/USD) to Composite Stock Price Index (CSPI) on the Stock Exchange Indonesia using the cointegration test and Vector Auto Regression (VAR) for the period 1995-2011. Cointegration test shows that there is a strong long-term balance between macroeconomic variables in the study of the JCI, while the test results of an analysis using Vector Auto Regression (VAR) indicates that there is an interplay of simultaneous relationships between macroeconomic variables in the study by CSPI.